2020
DOI: 10.1038/s41698-020-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multiomics analysis of hepatoblastoma unravels its heterogeneity and provides novel druggable targets

Abstract: Although hepatoblastoma is the most common pediatric liver cancer, its genetic heterogeneity and therapeutic targets are not well elucidated. Therefore, we conducted a multiomics analysis, including mutatome, DNA methylome, and transcriptome analyses, of 59 hepatoblastoma samples. Based on DNA methylation patterns, hepatoblastoma was classified into three clusters exhibiting remarkable correlation with clinical, histological, and genetic features. Cluster F was largely composed of cases with fetal histology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 47 publications
10
54
0
9
Order By: Relevance
“…We performed TCS for 381 pediatric cancer-related genes and regions (U-Tokyo Onco-panel ver.1) [ 24 ] ( S2 Table ) on 30 cases of INSS Stage 4 neuroblastoma ( S1 Table ). Each neuroblastoma sample harbored a mean of 4.2 variants (range = 1–10) ( S4 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed TCS for 381 pediatric cancer-related genes and regions (U-Tokyo Onco-panel ver.1) [ 24 ] ( S2 Table ) on 30 cases of INSS Stage 4 neuroblastoma ( S1 Table ). Each neuroblastoma sample harbored a mean of 4.2 variants (range = 1–10) ( S4 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Targeted capture was performed using a SureSelect custom kit (Agilent Technologies, Palo Alto, CA, USA) as previously described [24][25][26] The custom bait library (U-Tokyo Oncopanel ver.1) related to pediatric cancers (S2 Table) [24] was designed to include the following: (i) all coding exons of 367 genes; (ii) untranslated regions and introns of CD274, CTNNB1, ERG, ETV1, ETV4, EWSR1, FEV, FLI1, FOXO1, FUS, INO80D, NCOA1, NCOA2, NOTCH1, PAX3, and PAX7 for detecting breakpoints of structural variations; (iii) promoter and enhancer regions of FGFR3, MYC and TERT; (iv) microRNA genes MIR100, MIRLET7A1, MIRLET7A2, MIRLET7A3, MIRLET7B, MIRLET7C, MIRLET7D, MIRLET7E, MIRLET7F1, MIRLET7F2, and MIRLET7G; and (v) 3,527 positions of single nucleotide polymorphisms (SNP) for copy number analysis to generate genome-wide allele-specific copy number profiles. We selected 381 targeted genes and regions, not including the SNP positions, to include the following: (a) genes adopted in more than one of the following existing gene panels: MSK-IM-PACT27 CMS400 (Life Technologies, Carlsbad, CA, USA), FoundationOne (Foundation Medicine, Cambridge, MA, USA), or the Human Comprehensive Cancer Panel (QIAGEN, Hilden, Germany); (b) the most frequently mutated 20 genes in each type of malignancy according to the Catalogue of Somatic Mutations in Cancer (COSMIC) v78; and (c) genes that were recurrently affected in pediatric malignancies, including neuroblastoma, hepatoblastoma, pleuropulmonary blastoma, rhabdomyosarcoma, Ewing's sarcoma, and germ cell tumor.…”
Section: Targeted Capture Sequencing (Tcs)mentioning
confidence: 99%
“…[ 20 , 136 ]. In addition to Nrf2 and AhR mediated induction of NQO1, the methylation status of the NQO1 promoter may also be an important factor controlling NQO1 expression [ [137] , [138] , [139] , [140] ]. Mechanisms have also been proposed for the transcriptional regulation of NQO1 by antiestrogen-liganded estrogen receptor [ 95 , 96 ].…”
Section: Inducibility Of Nqo1 – Nrf2 and Ah Receptor Mediated Inductimentioning
confidence: 99%
“…Sekiguchi et al recently employed a multi-omics approach to classify 59 HBs [ 63 ], and showed that epigenetic changes are not only widespread but may also contribute to heterogeneous HB appearances and clinical behaviors. 56 of the tumors contained β-catenin mutations and an additional four contained APC gene mutations (i.e., a 100% incidence of Wnt/β-catenin/APC pathway dysregulation).…”
Section: Remaining Questionsmentioning
confidence: 99%